2018
DOI: 10.1111/eea.12643
|View full text |Cite
|
Sign up to set email alerts
|

Within‐diet variation in rates of macronutrient consumption and reproduction does not accompany changes in lifespan in Drosophila melanogaster

Abstract: Interventions such as caloric or dietary restriction extend lifespan in organisms spanning from yeast to primates. Despite its positive influence on longevity, dietary restriction has been found to negatively affect reproduction. Many studies have reported negative correlations between lifespan and reproductive characteristics (such as mating rate, fecundity, reproductive period, and others). Such correlation gives the appearance of a resource-based trade-off between these two life-history traits. Here, we hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…Carbohydrates were not show to have significant effects on lifespan or their impact is too weak [3,15]. However, recent findings have shown that dietary proteintocarbohydrate ratio (P:C) in the food is a key determinant of drosophila lifes pan [2,12,15]. Our study revealed, that low sucrose content in the diet maximized female lifespan.…”
Section: Resultsmentioning
confidence: 49%
See 1 more Smart Citation
“…Carbohydrates were not show to have significant effects on lifespan or their impact is too weak [3,15]. However, recent findings have shown that dietary proteintocarbohydrate ratio (P:C) in the food is a key determinant of drosophila lifes pan [2,12,15]. Our study revealed, that low sucrose content in the diet maximized female lifespan.…”
Section: Resultsmentioning
confidence: 49%
“…Fruit flies have become a promising model for studying the effects of dietary components on various physiological characteristics, including lifespan and metabolism. In studies on drosophila, new important knowledge was gained that the fun damental relationships between lifehistory traits are mediated by macroelements [12]. Using this model organism in the nutrition experiments help us to un derstand the relationship between human nutrition and metabolic disorders.…”
mentioning
confidence: 99%
“…Yeast in fly food can influence the lifespan and fecundity of the flies 2,5,[18][19][20] . Increased protein consumption or a high protein diet may lead to a shortened lifespan and higher fecundity 21 . Since our experimental setup involved both the AL and experimental (PR) flies maintained on AL food in the pre-adult stage, we assume that all the flies would have consumed the same amount of food in their pre-adult stage.…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in nutritional ecology show how an animal's diet can differently influence the expression of key life-history traits, lead-ing animals to trade off between optimizing multiple traits simultaneously (e.g., Bunning et al 2015Bunning et al , 2016Morimoto and Wigby 2016;Rapkin et al 2018). In insects, for instance, life span is typically enhanced on high-carbohydrate diets, whereas reproduction is maximized on high-protein diets (e.g., fruit flies [Lee et al 2008;Fanson et al 2009;Reddiex et al 2013;Jensen et al 2015;Semaniuk et al 2018], crickets [Maklakov et al 2008]). Immunity and reproduction also display complex species-specific differences in nutritional requirements (e.g., moths [Cotter et al 2011], fruit flies [Ponton et al 2015], crickets [Rapkin et al 2018]; reviewed in Ponton et al 2011;Schwenke et al 2016).…”
Section: Introductionmentioning
confidence: 99%